O livro didático de língua inglesa : legitimação do poder/saber - Gois, Amisa Dayane Lima de (2017)
As it is known to linguists and other professionals (whose object of study is language, communication), language is the way in which we interact with the social environment, with the other, in different contexts of use. In this sense, the subjects can use both their mother tongue (L1) and acquire any other language (L2), so that they can interact with the other language. Studying a foreign language (FL) and the consequent requirement for teaching at least one FL, in elementary school, it is then a right provided by the LDB. This teaching, in turn, is guided by the FL PCN, with prediction of a teaching / learning process focused on the interaction of the subject with the other, with their environment. Among the foreign languages, the English (hereinafter LI) is, in Brazil, the most taught in schools, given the great power, the American influence. As a result, we chose as our object of study the analysis of the discourses in circulation in the didactic textbook (later, LD) of LI, used in the public schools from Moita Bonita (SE), Vontade de Saber Inglês (KILLNER; AMANCIO), from the 6th to the 9th grade. From this perspective of research, we aim to contribute to the teaching of LI in our state and, more specifically, in this city. Because of this approach, our work is confined to two areas of knowledge: the Discourse Analysis (French line), based mainly on Orlandi's studies (1984, 2000, 2001, 2008); Applied Linguistics, from the point of view of Leffa (1999), Lima (2008). For the construction of our theoretical device, we counted with the contributions of Foucault (1997, 2003, 2009 [1969], 2012 [1978]), in the light of which we study the relations of power / knowledge established in the school; The question of authorship, observing from which place (social, institutional) the subject, in the position of author, states, which image does his interlocutor. In this way of approach, we also use the research of Grigoletto (1999), Carmagnani (1999), whose investigations are focused on LD. And, to understand the whole process of institutionalization of LI, its consequent adoption by Brazilian schools, we studied the historicization of the teaching of this LE; the language as a symbolic force, according to Bourdieu (s / d). We also searched the important documents, such as LDB (1996), PCN (1999), PNLD (referring to the three years of the book in question). As a methodological research resource, to the construction of our analysis device, we made the following research questions: What speeches are circulating in LD LI? What approaches do the authors make of these discourses? From which place (social, institutional) does the author / speaker of the LD of LI state? What ideologies are pervaded in these discourses? What is the image that the subject author of the LD of LI makes of his interlocutor (student)? In order to answer these guiding questions, we use Orlandi's contributions (1984), taking five discursive cut-outs from the LI textbook collection. According to this analyst, these cuts are discursive units, fragments of discursive situations. We then make the following discursive cuts: the discourse of / about society, the discourse of / about grammar, the avertising discourse, the discourse of / about youth, the discourse of / about school. These cutouts were thus organized according to their incidence in this collection. Through these settings, we understand that the relevance of our investigations is to look the LD in a discursive way, trying to interrelate these areas of knowledge (the AD and the LA). We understand, finally, that this multiple view contributes to the constitution of the LI teachers subjects, especially regarding the fact that, from reading this work, they are able to reflect on the relations of power / knowledge established in the school.